Are we changing planet earth? - Films For The Humanities & Sciences (Firm); The Open University (Princeton, N.J. : Films for the Humanities & Sciences, 2008)
This program presented by Sir David Attenborough discusses the thickening of Earth's carbon dioxide envelope and, using climate modeling, confirms that fossil fuels are primarily responsible for a global rise in temparatures going far beyond any normal allowance for cyclical fluctuation. Traveling from the Artic, where the ecosystem is collapsing; to the lowlying islands of the South Pacific, where flooding in now chronic; to the bleaching Great Barrier Reef, the program offers definitive evidence of global warming: retreating glaciers, rising seas, stronger hurricanes, severer droughts, enroaching deserts, and a biosphere that is visibly in decline
Presenter: Sir David Attenborough
Keywords: Climate changes; Climatic changes -- Environmental aspects; Global environmental change